Pemilihan Konstruksi Penaggulangan Longsoran Atas Pada Ruas Jalan Poros Palopo - Bastem - Toraja Desa Bonglo, Kecamatan Bastem Utara - Citra Angela; Syahrul Sariman; Eka Yuniarto (Program Studi Teknik Sipil Universitas Bosowa, 2026)
The Palopo-Bastem-Toraja axis road that crosses mountainous and valley areas in North Bastem Sub-district has sandy loam soil conditions that tend to be unstable and prone to landslides. Field observations show that there are eight landslide-prone points along the Latuppa-Bastem road section, with a major landslide occurring in Bonglo Village on February 26, 2024. This landslide was triggered by high rainfall intensity, lack of road safety structures, and caused material losses and casualties. This research aims to analyze the physical properties of the soil at the landslide site as a basis for retaining wall planning. Soil testing in the laboratory showed the soil at location 1 point 1 clay mixed with sand (0 - 1 meter), point 2 silt mixed with gravel (2 - 10 meters), and at location 2 point 1 clay mixed with sand (0 - 3 meters), point 2 silt mixed with gravel (3 - 10 meters). Slope stability analysis using Bishop's method indicates a safety factor of 0.98 < 1.05, indicating the condition of the slope is unsafe. The retaining wall chosen in this research is the Cantilever Wall, after designing the dimensions of the retaining wall, by controlling the safety of overturning, shearing and bearing capacity. From the design results, the rolling FK is 4.487, the sliding FK is 2.812, and the bearing capacity is 3.089, which shows the safety figures required in the SNI geotechnical design requirements